Disease Prevention, Genetic Selection, and Vaccination Based on BoLA-DRB3.2 Polymorphism: A Model for Immunogenetic Studies - Mohammad Mehdi Ranjbar; Ali Reza Yousefi; Mohammad Hasan Motedayen; Shima Molazadeh; Gholamreza Karimi (Fasa University of Medical Sciences, 2022)
Unearthing the immune defects associated genes and genetic variations may lead to locating novel targetable elements and introducing the underlying mechanisms and pathways of the desired condition. The major histocompatibility complex (MHC) genes are essential for protein antigens presentation and inducing immune response as well as are associated with production and phenotypic traits. The MHC class II genes of cattle and buffaloes, Bovine Leukocyte Antigen (BoLA) or Buffalo Leukocyte Antigen (BuLA), are located on the short arm of chromosome 23. It has been demonstrated that the second exon of BoLA-DRB3 (BoLA-DRB3.2) is highly polymorphic, having more than one hundred identified alleles, that each of them can form special binding pockets for corresponding antigenic peptides. Concerning the populations of cows, unique native and hybrid, and buffaloes are distinctly divided into different regions of Iran, analysis and interpretation of the polymorphisms' expression status of this locus can be implemented to find better breeding strategies like selecting highly resistant animals to infection diseases, in herds. It also can help to develop effective and novel vaccines regarding allele frequencies in populations; different allelic variants of MHC class II binding to different peptides. Immunogenic evaluation of animals' genome/genes characteristics has always been used as a model for the study of similar genes in humans.